Preliminary evidence of the association between monochlorinated bisphenol A exposure and type II diabetes mellitus: a pilot study - Andra, Syam S.; Andrianou, Xanthi; Makris, Konstantinos C.; Christophi, Costas A.; Charisiadis, Pantelis; Kalyvas, Harris (My University, 2015)
Evidence for the association of bisphenol A (BPA) with type II diabetes mellitus (T2DM) has been inconsistent in human studies. In-vitro and animal studies indicate that chlorinated BPA derivatives aggravate BPA health effects via higher estrogenic activity and alteration of membrane-initiating signaling pathways. We evaluated the association between urinary monochlorinated BPA (mono-ClBPA) concentrations and the incidence of T2DM. In our cross-sectional study, we identified 20 adult participants (≥18 yr) who reported having T2DM (doctor-diagnosed) and 131 adults with normal health. First morning void urine samples were analyzed for total BPA and mono-ClBPA. Detection limits of the analytical method were 95 ng L−1 for BPA and 32 ng L−1 for mono-ClBPA. Multivariable logistic regression analyses and additive Bayesian network modeling were performed. After adjusting for age, gender, BMI, urinary total BPA and other confounders, the odds of having T2DM was 3.29 times higher (95% confidence interval, CI: 1.10, 11.4; P < 0.05) per unit increase in log-transformed and creatinine-adjusted urinary mono-ClBPA levels (n = 151); this relation did not hold for total BPA. The globally optimum Bayesian model corroborated the results of the logistic regression by expressing mono-ClBPA in the pathway of T2DM, and not for total BPA. An age-matched sensitivity analysis confirmed the increase in OR of T2DM by 3.04 times (95% CI: 1.10, 11.0; P < 0.05) per unit increase in log-transformed and creatinine-adjusted urinary mono-ClBPA concentration (n = 68). The urinary monochlorinated BPA derivative was significantly associated with T2DM, whereas the parent compound (total BPA) was not. Caution should be applied in interpreting these findings, as this is the first study to report this association and the sample size of participants with T2DM is small. Additional research with a larger sample size coupled with relevant toxicological studies is warranted.
Keywords: Bisphenol A; Exposure biomarkers; Monochlorinated bisphenol A; Type 2 diabetes; Trihalomethanes